Power Generation Monitoring of a hybrid Power System with I-GWO designed trapezoidal type-II fuzzy Controller. (3rd September 2022) - Mishra, Debashish; Sahu, Prakash Chandra; Prusty, Ramesh Chandra; Panda, Sidhartha
ABSTRACT: This article has implemented a robust type-II fuzzy PID controller for automatic generation control (AGC) of a diverse energy source-based multi-area power system under various operating conditions. The AGC aims to make stability over frequency and tie-line power of the power system. The proposed controller is accessed with Type-II Fuzzy systems with trapezoidal-based membership functions. In controller design concern, a novel soft computing algorithm called an improved-grey wolf optimizer (I-GWO) is approached for this study. The performance of the proposed trapezoidal membership function-based type-II fuzzy controller (TM-T2FC) has been extensively compared with the existing triangular membership-function based fuzzy-II controller (TrM-T2FC), type-I fuzzy controller (T1FC) and PID controller for AGC of the multi-area power system. Furthermore, the viability and effectiveness of the anticipated I-GWO algorithm have been separately assessed through suitable comparative studies. The robustness of the proposed TM-T2FC controller is investigated through different sensitive analyses and further assessment has been carried out by extending the proposed controller to a five area power system. It is observed from extensive studies and performance assessment that the proposed TM-T2FC controller can be a potential candidate for the AGC of the multi-area power system.